Pergeseran Kebijakan Strategis AS-Tiongkok: Transisi kekuasaan Era Biden ke Trump 2.0 - Larasati, Larasati (Lampung Center for Global Studies (LCGS), 2025)
Abstract This study aims to analyze the transition of the United States government from the Biden administration to Trump 2.0, with a focus on the dynamics of US-China relations and the sustainability of the America First policy. Using the Foreign Policy Change theory, this study examines the paradigm shift in US foreign policy from the Democratic Party leadership in the Biden-Harris era to the Republican Party approach under Trump, particularly in the areas of economic, trade, and security policies. Drawing on Charles Hermann's foreign policy change model and Graham Allison's bureaucratic politics approach, this study examines how the administration transition influences the direction of strategic relations between the two world powers. The research findings show that Trump's return has the potential to strengthen the direction of unilateralism and strategic rivalry towards China, but at the same time opens up the possibility of forming a new order in international relations. This study provides theoretical contributions to the study of foreign policy change as well as practical implications for policymakers and diplomatic actors in responding to the direction of US foreign policy during the Trump 2.0 administration. Keywords: US Foreign Policy, US–China Relations, America First, Trump 2.0, Strategic Rivalry